Recent developments in evaluation methods and characteristics of comfort environment in underground subway - Yan, Weichao; Meng, Xiangzhao; Zhou, Haiyun; Yang, Chuanjun; Chen, Qian; Oh, Seung Jin; Cui, Xin (Frontiers in Built Environment, 2022)
In recent years, due to the rapid progress of urbanization, the subway system with the advantages of large transport capacity, punctuality, efficiency, convenience and safety has become one of the main transportation modes in metropolitan areas. With the increase in passenger flow, the comfort of subway passengers has attracted extensive attention from the academic community. In this paper, we begin by analyzing the characteristics of the subway environment and sort out six environmental elements that affect passengers’ comfort, including thermal environment, vibration, noise, lighting, air quality, and air pressure. In addition, the measurement scheme, calculation model, and evaluation method of each element are outlined based on relevant norms and literature. Through reviewing the studies in the past two decades, it is found that the in-depth research is still in demand for a comprehensive comfort evaluation model with multi-element coupling. A deep understanding of the subway passengers’ comfort is the basis for the design, development, and operation regulation of the subway environmental control system. Measures to improve comfort, especially the exploitation of energy-saving air conditioning systems, will provide strong support for the sustainable and sound growth of the rail transit industry.